From Peripatetic Anthropology to the Ethnography of Roads and Motorisation in Africa - Horta,Gerard (2019)
This paper is based on 10 months of field work between 2009 and 2014 in Cape Verde, and provides an overview of the anthropological literature in which motor vehicles and African roads are studied as social phenomena. Until the end of the twentieth century, most ethnographies have failed to focus on the countless social processes linked to the development of mobility by road and the motorisation of transportation in Africa, or on the role played by cars and roads as symbols of a globalised modernity. The paper reviews the research by authors who, from the 1930s onwards, mention African roads and the use of motor vehicles as spaces in which social situations and processes take place. The several symbolic and instrumental dimensions of the motorisation of road transportation in Africa are discussed as well.